Marvin Lee Minsky: pioneer in artificial intelligence research (1927-2016) (Publicaciones en Ciencias y Tecnología, 2021)
Artificial Intelligence and its name owe its beginnings to the sum of efforts of scientists around the world with the idea of equipping machines with human capabilities. Marvin Lee Minsky was one of them. This eminent mathematician born in New York in the decade of the 20s had revolutionary ideas in the way in which human intelligence is conceived and in machines. Inventor, innovator and philosopher Marvin Minsky dedicated his life to the end of his days to the understanding of how we develop our intelligence and from this knowledge generate systems whose capabilities match and even exceed human. A man's life can be measured by his contributions to the advancement of humanity and the degree of passion that drives him to work tirelessly to achieve that contribution. This review aims to present a brief biography of Marvin Lee Minsky, presenting him from a scientific point of view through his most relevant contributions and his contributions to the research and development of Artificial Intelligence.
Keywords: Minsky; artificial intelligence; biography